Uricosuric activity of Tinospora cordifolia (Bangladesh Journal of Pharmacology, 2015)
Uricosuric activity of different extracts of Tinospora cordifolia was studied in hyperuricemia induced in albino Wistar rat using potassium oxonate. The uric acid level in serum and urine were measured.  Uricosuric activity was also evaluated using phenol red dye excretion model.  Phenol red levels were measured in blood. In potassium oxonate induced hyperuricemia, probenecid, aqueous, hydro-alcoholic, dichloromethane extract and galo satwa (starch of T. cordifolia) significantly lowered the serum uric acid levels. All the extracts increased uric acid excretion and decreased the elevated serum uric acid levels induced due to potassium oxonate. Probenecid, aqueous extract and galo satwa significantly increased fractional excretion of uric acid and phenol red levels in blood indicating uricosuria. Polysaccharides in aqueous extract and galo satwa may be responsible for uricosuric action. Video Clips of Methodology:Preparation of extracts                             4 min 22 secPrepared extracts                                            26 sec      Potassium oxonate induced hyperurecimia   1 min 46 secInjection of red phenol into tail vein                    52 secCollection of blood                                           16 secEstimation of uric acid                             1 min 44 sec